Structural and electrical properties of CdO/porous-Si heterojunction - Ismail, Raid A. (Iraqi Journal of Physics, 2012)
The electrical properties of CdO/porous Si/c-Si heterojunction prepared by deposition of CdO layer on porous silicon synthesized by electrochemical etching were studied. The structural, optical, and electrical properties of CdO (50:50) thin film prepared by rapid thermal oxidation were examined. X-ray diffraction (XRD) results confirmed formation of nanostructured silicon layer the full width half maximum (FWHM) was increased after etching. The dark J-V characteristics of the heterojunction showed strong dependence on etching current density and etching time. The ideality factor and saturation current of the heterojunction were calculated from J-V under forward bias. C-V measurements confirmed that the prepared heterojunctions are abrupt type .The value of built-in-potential as function of etching current density was estimated.